Меню

УСЛОВИЕ:
Раскрыть скобки и привести подобные слагаемые 4(х+2)-3(5-х)-х-3
3(х+3)-4(3-х)-(4+3)х-3
5(х+4)-(5-х)-х-3
4(х+1)-5(5-х)-(5+4)х-1
2(х+2)-5(4-х)-(5+2)х-3
4(х+1)-4(3-х)-х-5
2(х+4)-(2-х)-(1+2)х-1
х+4-2(5-х)-х-4
х+5-(2-х)-(1+1)х-1
5(х+1)-2(5-х)-х-3


РЕШЕНИЕ:

4(х+2)-3(5-х)-х-3=4х+8-15+3х-х-3=6х-10=2(3х-5)
3(х+3)-4(3-х)-(4+3)х-3=3х+9-12+4х-4х-3х-3=-6
5(х+4)-(5-х)-х-3=5х+20-5+х-х-3=5х+12
4(х+1)-5(5-х)-(5+4)х-1=4х+4-25+5х-5х-4х-1=-22
2(х+2)-5(4-х)-(5+2)х-3=2х+4-20+5х-5х-2х-3=-19
4(х+1)-4(3-х)-х-5=4х+4-12+4х-х-5=7х-13
2(х+4)-(2-х)-(1+2)х-1=2х+8-2+х-х-2х-1=5
х+4-2(5-х)-х-4=х+4-10+2х-х-4=2х-10=2(х-5)
х+5-(2-х)-(1+1)х-1=х+5-2+х-х-х-1=2
5(х+1)-2(5-х)-х-3=5х+5-10+2х-х-3=6х-8=2(3х-4)






Похожие примеры: